Find this integral ∫ 0 1 ln x ln ( 1 − x ) d x .
Hint: n = 1 ∑ ∞ n 2 1 = 6 π 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The integral in the question is undefined. It should be I = ∫ 0 1 ln x ln ( 1 − x ) d x
Now, to solve the integral, simply expand it using ln ( 1 − x ) = − n = 1 ∑ ∞ n x n and then, switching the summation and integral sign, we have
∫ 0 1 ln x ln ( 1 − x ) d x = − n = 1 ∑ ∞ ( ∫ 0 1 n x n ln x d x )
Substituting ln x = − t we have
I = n = 1 ∑ ∞ ( ∫ 0 ∞ n t e − ( n + 1 ) t d t )
= n = 1 ∑ ∞ ( n + 1 ) 2 n 1
= n = 1 ∑ ∞ n ( n + 1 ) 1 − n = 2 ∑ ∞ n 2 1
= 1 − ( 6 π 2 − 1 )
Thus making the answer 2 − 6 π 2
Thanks, I changed.
Integrating with dt or what typo.
First, we need to turn the integrand function into a series and integrate everything term by term. We have
ln x ln ( 1 − x ) = ln x ( − x − 2 x 2 − 3 x 3 − . . . ) = n = 1 ∑ ∞ n − ln x x n . ( 1 )
Now it is possible to integrate every term of the sequence by parts:
0 ∫ 1 n − ln x x n d x = − n ( n + 1 ) 1 0 ∫ 1 ln x d ( x n + 1 ) =
= − n ( n + 1 ) 1 ( ln 1 ⋅ 1 n + 1 − x → 0 + lim ln x ⋅ x n + 1 ) +
+ n ( n + 1 ) 1 ∫ 0 1 x n + 1 d ( ln x ) = n ( n + 1 ) 1 ∫ 0 1 x n d x = n ( n + 1 ) 2 1 . ( 2 )
Can we integrate the series? In order to make sure in the validity of our actions ( 1 ) , we should show that for all ε > 0 there is such m 0 ∈ N , that
∣ ∣ ∣ ∣ ∣ 0 ∫ 1 ln x ( ln ( 1 − x ) + n = 1 ∑ m n x n ) d x ∣ ∣ ∣ ∣ ∣ < ε , for all m ≥ m 0 . ( 3 )
On given ε > 0 , let's choose δ ∈ ( 0 , 1 / 2 ) , so that:
∣ ∣ ∣ ( 0 ∫ δ + 1 − δ ∫ 0 ) ln x ln ( 1 − x ) d x ∣ ∣ ∣ < ε / 2 . .
Taking into account this double inequality
ln ( 1 − x ) < ln ( 1 − x ) + n = 1 ∑ m n x n < 0 ,
we will get
∣ ∣ ∣ ( 0 ∫ δ + 1 − δ ∫ 0 ) ln x ( ln ( 1 − x ) + n = 1 ∑ m n x n ) d x ∣ ∣ ∣ < ε / 2 . ( 4 )
Since in the interval [ δ , 1 − δ ] the function ln x ( ln ( 1 − x ) + n = 1 ∑ m n x n ) uniformly equals to zero for m → ∞ , for some big enough m
∣ ∣ ∣ ∣ ∣ δ ∫ 1 − δ ln x ( ln ( 1 − x ) + n = 1 ∑ m n x n ) d x ∣ ∣ ∣ ∣ ∣ < ε / 2 .
Adding up this inequality and ( 4 ) , we get required inequality ( 3 ) for all m ≥ m 0 .
Now, we can integrate ( 1 ) , we find the value of the integral:
0 ∫ 1 ln x ⋅ ln ( 1 − x ) d x = n = 1 ∑ ∞ n ( n + 1 ) 2 1 = n = 1 ∑ ∞ ( n ( n + 1 ) 1 − ( n + 1 ) 2 1 ) =
= n = 1 ∑ ∞ ( n 1 − ( n + 1 ) 1 ) − n = 2 ∑ ∞ n 2 1 = 1 − ( n = 1 ∑ ∞ n 2 1 − 1 ) = 2 − 6 π 2 = − 0 . 3 5 5 .
Problem Loading...
Note Loading...
Set Loading...
∫ ( lo g x ) ( lo g ( 1 − x ) ) d x = − Li 2 ( x ) − x ( lo g ( x ) − 2 ) + ( x − 1 ) lo g ( 1 − x ) ( lo g ( x ) − 1 ) + constant .
x → 0 lim ( − Li 2 ( x ) − x ( lo g ( x ) − 2 ) + ( x − 1 ) lo g ( 1 − x ) ( lo g ( x ) − 1 ) ) ⇒ 0 .
x → 1 lim ( − Li 2 ( x ) − x ( lo g ( x ) − 2 ) + ( x − 1 ) lo g ( 1 − x ) ( lo g ( x ) − 1 ) ) ⇒ 2 − 6 π 2 .
Both limits of the indefinite integral are necessary.